Shaykh Dawud al-Fatani's Manhal al-Safi: An Annotated Transliteration - Abd. Rahman, Mohd. Zain (Afkar: Jurnal Akidah dan Pemikiran Islam, 2007)
This paper, which is the continuation of the previous paper published in Afkar 2005, presents an annotated transliteration of the Malay Jawi text of al-Manhal al-Safi written by Shaykh Dawud al-Fatani. The preparation of the romanized edition of this classical jawi text is done with full cautions and faithful to the text without making any amendment and alteration to the word(s) and structure of the Malay language used in the text. We have done so in order to preserve the originality of the text as well as to highlight the style of the Malay language used by the author that represents the style used during the early period of the 19th century. With this approach, we believe to do justice to the original author and to ensure the originality of the text, thus, to avoid any misleading to the meaning intended by the author if we simply amend and alter the language structure in accordance to the current usage of the Malay language.